Mutable Reality and Unknowable Future: Revealing the Broader Potential of Pragmatism - Sergeeva, Anastasia; Bhardwaj, Akhil; Dimov, Dimo (Academy of Management Review, 2022)
In this dialogue paper, we consider Zellweger and Zenger’s (2021) conceptualization of entrepreneurs as scientists, rooted in pragmatism. While we agree that pragmatism provides a useful but neglected foundation for studying the entrepreneurial journey, we maintain that entrepreneurs are more than scientists – in addition, they are engineers, artists, and designers. Our view is predicated on enfolding considerations of time, emergence, and the associated unsurmountable epistemological barrier of unknowability, which enable entrepreneurs to not only describe (predict) the world as scientists do, but also actively shape the future to fit their “mind.”